The effect of durvalumab consolidation after definitive radiochemotherapy for non-operable stage III non-small cell lung cancer on the dose effect relation for therapy related pulmonary infiltrates as a risk factor for pneumonitis - Herz, Andreas; Guberina, Maja; Pöttgen, Christoph; Gauler, Thomas; Ton, Mike; Fischedick, Gerrit; Kiwitt, Lars Oliver; Lübcke, Wolfgang; Hoffmann, Christian; Schuler, Martin; Metzenmacher, Martin; Schaarschmidt, Benedikt M.; et al. (Translational Lung Cancer Research, 2025)
Background: Consolidation therapy with the anti-programmed death-ligand 1 (PD-L1) antibody durvalumab, or other immune checkpoint inhibitors, has been associated with improved progression-free and overall survival in patients with stage III non-small cell lung cancer (NSCLC) as demonstrated in randomized clinical trials. The purpose of the present study is to evaluate the dose-response relationship for partial lung infiltrate volumes per dose bin after definitive radiochemotherapy as a sensitive end point to detect a durvalumab effect on the lung parenchyma in patients with subclinical or grade ≤2 pneumonitisMethods: Consecutive patients from a prospective registry with inoperable NSCLC stage III whodeveloped no or pneumonitis grade ≤2 after definitive radiochemotherapy with or without durvalumab consolidation were included. Pulmonary infiltrates outside the planning target volumes were contouredin the follow-up computed tomography (CT) at the time of maximum infiltrate expression. Partial lunginfiltrate volumes per dose bin were determined over the entire dose range. A mixed random and fixed effect model was used to fit dose response curves stepwise in dose bins of 5 Gy. The Akaike information criterion (AIC) was used for model comparison.Results: Sixty patients with and 44 without durvalumab consolidation were analysed. The step modelshowed a significant dose response relationship for the pulmonary infiltrates (P<0.001, F-test) that was modified by the durvalumab effect (P<0.001, F-test). There was a significant dependence of the durvalumab effect on radiation dose (P=0.003). The durvalumab effect increased with dose from 0% in the lowest dosebin as reference to 5.2%±1.2% partial lung infiltrate volume in the highest dose bin. There was significant inter-individual heterogeneity of partial lung infiltrate volumes at each dose bin (P<0.001, F-test).